2007
DOI: 10.1187/cbe.06-10-0198
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Instruction in Introductory Biology I: Enhancing the Performance and Retention of Underrepresented Minority Students

Abstract: Supplemental instruction classes have been shown in many studies to enhance performance in the supported courses and even to improve graduation rates. Generally, there has been little evidence of a differential impact on students from different ethnic/racial backgrounds. At San Francisco State University, however, supplemental instruction in the Introductory Biology I class is associated with even more dramatic gains among students from underrepresented minority populations than the gains found among their pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 6 publications
6
49
2
Order By: Relevance
“…Students who identify as underrepresented minorities (URMs)-African Americans, Native Americans, Hispanics, and Pacific Islandersare particularly likely to steer clear of science careers (Summers and Hrabowski, 2006). Members of these groups earn only 14.6% of biology and 11% of physics bachelor's degrees, according to the most recent data available from the National Center for Education Statistics (2005Statistics ( -2006, while earning 24.8% of liberal arts degrees, a percentage which is more in line with the proportion of URMs in the general population (Rath et al, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…Students who identify as underrepresented minorities (URMs)-African Americans, Native Americans, Hispanics, and Pacific Islandersare particularly likely to steer clear of science careers (Summers and Hrabowski, 2006). Members of these groups earn only 14.6% of biology and 11% of physics bachelor's degrees, according to the most recent data available from the National Center for Education Statistics (2005Statistics ( -2006, while earning 24.8% of liberal arts degrees, a percentage which is more in line with the proportion of URMs in the general population (Rath et al, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…While many studies have been conducted on prior academic experiences (e.g., Dobson 2008;Eddy et al 2014;Orr and Foster 2013;Rath et al 2007;Richardson et al 2012;Lee et al 2008), much less work has explored the utility of information gathered during students' current academic experiences. Concept inventory (CI) and clicker data are increasingly used in large STEM classes and may be useful data sources for predicting student performance at an actionable point in the semester (i.e., earlier than a midterm report).…”
Section: Early Warning Systems In Stem Educationmentioning
confidence: 98%
“…A central feature of EWS is a predictive algorithm developed using data from current and past student performances. Many additional variables, such as gender, ethnic background, English language learner (ELL) status, and other constructs (e.g., personality, self-efficacy), may be incorporated into EWSs given that these factors have been shown to be correlated with academic success (Dobson 2008;Eddy et al 2014;Orr and Foster 2013;Rath et al 2007;Richardson et al 2012;Lee et al 2008).…”
Section: Early Warning Systems In Stem Educationmentioning
confidence: 99%
“…The support of Supplemental Instruction through small group skill development has proven to make positive waves in learning scientific concepts and problem-solving among underrepresented students, which include women and minority students (Lundberg, 1995;Rath et al, 2007;Shaya, Petty, & Petty, 1993). Supplemental Instruction can be applied to a diverse scale of subjects; nonetheless, it has shown to be effective in teaching scientific concepts and contributing to the success of students in the sciences (Congos & Mack, 2005;Gaddis, 1994;Gattis, 2002;Lundeberg, 1990;Lundeberg & Moch, 1995;Parkinson, 2009).…”
Section: Science Successmentioning
confidence: 99%
“…The grant's intent of was to increase the number of Hispanic and low income students attaining degrees in STEM fields. Given that research has shown that Supplemental Instruction has been effective in increasing success in science (Parkinson, 2009;Rath et al, 2007;Kenney & Kallison, 1994;Shaya, Petty, & Petty, 1993), it was chosen as the academic support program to be implemented. This study's purpose was to determine if Supplemental Instruction affected final grades in science courses and course completion among Hispanic students at a public, four-year south Texas HSIs.…”
mentioning
confidence: 99%